Policultivos: abordagens científicas e suas avaliações - Bosso, Victor Salek (Universidade Federal de São Carlos, 2026)
Intercrop systems can enhance productivity and profitability while improving the social and environmental conditions of their surroundings. However, despite extensive research on the topic, the relevant factors for their evaluation and optimization—essential for widespread adoption—have not been systematically identified. This study analyzes the evaluation factors prevalent in high-impact publications indexed in the Web of Science (WoS) and identifies research gaps in intercrop studies. The methodology was based on a literature search using the keywords: intercrop OR polyculture OR polycultural OR polycrop. An individual analysis of the retrieved articles highlighted the leading journals, main WoS categories, agricultural crops used in intercrops, and the factors studied within Agronomic (80%), Environmental (11%), Economic (6%), and Social (4%) approaches. Merely 37% of the studies adopted a multi- or interdisciplinary perspective, considering at least two of these frameworks. The categories 'Agronomy' and 'Plant Science' collectively account for 40% of the articles. Furthermore, 33% of the analyzed publications were concentrated in just 5 out of 210 relevant journals. The study also discusses the limitations of a disciplinary approach that favors specific fields of agricultural science over interdisciplinary approaches and indicates gaps and opportunities for future research.
Intercropping: scientific approaches and their evaluations
Keywords: Agricultura Sustentável; Consórcios; Interdisciplinaridade; Revisão de escopo; Polyculture; Interdisciplinarity; Sustainable agriculture; Scope review; CIENCIAS AGRARIAS; 2. Fome Zero e Agricultura Sustentável; 8. Trabalho Decente e Crescimento Econômico; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre